The Influence of Time Management, Learning Environment and Intellectual Ability on Timely Completion of Thesis (Case Study of Management Department Students, Faculty of Economics and Business, University of Riau Class 2017-2019) - Fadhilah, Fitri; Hendriani, Susi; Tarigan, Mida Aprillina (Journal Of Accounting Management Business And International Research, 2025)
This study aims to determine the influence of time management, learning environment, and intellectual ability on timely thesis completion among students of the Management Department, Faculty of Economics and Business, Universitas Riau, class of 2017-2019. The population consisted of 370 active students in the thesis completion stage. The sampling technique employed Slovin's formula to determine the sample size for each sub-population using proportionate stratified random sampling. The analysis method utilized in this study was Structural Equation Modeling (SEM) processed using SmartPLS version 4.1.0.3. The results of hypothesis testing indicated that Time Management significantly influences Timely Thesis Completion with a positive correlation. Learning Environment does not significantly influence Timely Thesis Completion with a positive correlation. Intellectual Ability significantly influences Timely Thesis Completion with a positive correlation.